THE DEFFEREN SERVICE QUALITY PUBLIC HOSPITALS WITH PRIVATE HOSPITALS ON OUTPATIENTS BPJS CARD USERS - Winbaktianur, Winbaktianur; Rizqi, Nova (Universitas Islam Negeri Imam Bonjol Padang, 2016)
The hospital is one of the health facilities where conduct health efforts. Hospital in Indonesia two kinds of hospitals, that is public hospital and private hospital. Every public and private hospitals are obliged to provide good services for each patient, including the patient BPJS. The purpose of this study to determine differences service quality public hospitals with private hospitals on outpatients BPJS card users.This research included in the quantitative research. Measuring instruments used in this study is the scale modification using the service quality theory Parasuraman, Zeithaml, and Berry (1988) which consists of five aspects: tangibles, reliability, responsiveness, assurance and empathy totaling 50 aitem. Population in this study is outpatients BPJS card users in the installation of outpatient surgery public hospitals X and private hospitals Y. Total of samples used in this study were 150 patients. Consist of 75 public hospital X outpatients and 75 private hospital Y outpatients. Sampling technique used is non probability sampling with accidental sampling. Data analysis technique used is t-test (independent sample t test).The result of this study indicate that there is no difference in the quality of service of public hospital X and private hospital Y on outpatients BPJS card users. This is evidenced by the result of the t test arithmetic is 0,759 with significant value is 0,449. This suggests that public hospital X and private hospital Y provide equal services to outpatients BPJS card users. This study also shows that the quality of services public hospital X and private hospital Y that are in either category.